Farm Type Effects of an EU‐wide Direct Payment Harmonisation. (24th January 2013) - Gocht, Alexander; Britz, Wolfgang; Ciaian, Pavel; Paloma, Sergio Gomez y
Abstract In this study, we analyse how three scenarios involving different levels of harmonisation of common agricultural policy (CAP) decoupled payments in the EU affect the distribution of farm income across regions and farm types. We use the farm type extension of the common agricultural policy impact (CAPRI) model, which captures farm heterogeneity across the EU. The first scenario (NUTS1) assumes uniform per‐hectare payments at the NUTS1 level. The second scenario (MS‐CONV) equalises the per‐hectare rates inside each Member State (MS) and partially harmonises the single payment scheme (SPS) across MS in line with the 2011 Commission proposal. The third scenario simulates a uniform per‐hectare payment at the EU level. Depending on the implementation of the SPS, the NUTS1 flat rate induces a substantial redistribution of payments across farm types and NUTS2 regions, particularly in regions that apply the historical SPS. The MS‐CONV and EU flat‐rate schemes have more significant impacts at the EU‐wide level. In the EU‐15, almost all farms lose payments from MS‐CONV and EU‐wide flat rates, whereas in the EU‐10, almost all farm types gain from these scenarios. Our conservative estimates indicate that the flat‐rate payments could redistribute up to €8.5 billion. Lower land rental costs partially offset the losses of farm income in the EU‐15 from payment redistribution. Land rents drop for all flat‐rate scenarios across most sectors and farm sizes in the EU‐15. In the less productive new MS, the landowners' rental income is largely unaffected by the introduction of the flat rate.